An improved method for estimating the Ångström turbidity coefficient β in Central China during 1961–2010. (1st March 2015) - Wang, Lunche; Salazar, Germán Ariel; Gong, Wei; Peng, Simao; Zou, Ling; Lin, Aiwen
Abstract: The accurate determination of the atmospheric turbidity is of great importance for atmospheric environment, solar energy applications and climate change studies. Daily values of horizontal direct, diffuse and global solar radiation at Wuhan, Central China during 1961–2010 are used for estimating the monthly mean Ångström turbidity coefficient β . The YHM and YHM2 (Yang hybrid models) are first used to estimate the direct and diffuse components considering the transmittances of ozone, water vapor, gas mixture, aerosol and Rayleigh effect in the radiative transfer processes. An IMW (improved model for Wuhan) is also proposed by combining the format of YHM model with the corrected spectral terms of YHM2 model. Then, the β value can be estimated by varying the estimated direct irradiation until it matches the observation. The model performance is analyzed and compared and further validated by measured values using Sun photometer CE318. It is shown that the IMW model presents more accurate estimates than YHM and YHM2 ones; it is therefore a useful tool for studying the variability and evolution of atmospheric turbidity in other places around the world. Highlights: Global, direct and diffuse radiation at Wuhan during 1961–2010 is used. An improved model is proposed to determine turbidity coefficient β . The model results have been validated by field observations. Long-term variations of turbidity coefficient at Wuhan are analyzed.